2020
DOI: 10.3390/jof7010006
|View full text |Cite
|
Sign up to set email alerts
|

Replicative Aging in Pathogenic Fungi

Abstract: Candida albicans, Candida auris, Candida glabrata, and Cryptococcus neoformans are pathogenic yeasts which can cause systemic infections in immune-compromised as well as immune-competent individuals. These yeasts undergo replicative aging analogous to a process first described in the nonpathogenic yeast Saccharomyces cerevisiae. The hallmark of replicative aging is the asymmetric cell division of mother yeast cells that leads to the production of a phenotypically distinct daughter cell. Several techniques to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…The total number of buds that a mother cell produces before the division ceases and dies is the designated replicative life span (RLS). Each cycle of bud formation by a mother cell represents one generation [ 75 ]. Several studies showed that replicative ageing in many fungal pathogens leads to significant changes that affect the fungal resistance to phagocytic clearance and antifungal therapy [ 75 ].…”
Section: Candida Glabrata Virulence Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of buds that a mother cell produces before the division ceases and dies is the designated replicative life span (RLS). Each cycle of bud formation by a mother cell represents one generation [ 75 ]. Several studies showed that replicative ageing in many fungal pathogens leads to significant changes that affect the fungal resistance to phagocytic clearance and antifungal therapy [ 75 ].…”
Section: Candida Glabrata Virulence Factorsmentioning
confidence: 99%
“…Each cycle of bud formation by a mother cell represents one generation [ 75 ]. Several studies showed that replicative ageing in many fungal pathogens leads to significant changes that affect the fungal resistance to phagocytic clearance and antifungal therapy [ 75 ]. The phenotypic changes in the daughter cells due to ageing are not genetically inherited.…”
Section: Candida Glabrata Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, beyond molecular mechanisms of antifungal resistance in C. auris , phenotypic modifications and biofilm formation also influence the degree of drug resistance [ 61 , 108 , 110 ]. As previously stated, replicative aging resulting in asymmetric cell division and phenotypically distinct daughter cells has been associated with increased virulence, but also drug resistance [ 111 , 133 ]. Senescent C. auris cells showed a higher tolerance to fluconazole, micafungin, flucytosine, and amphotericin B. Bhattacharya et al [ 111 ] demonstrated that fluconazole resistance in these cells was due to gene duplication in CDR1 and ERG11.…”
Section: Microbiological Features Of C Aurismentioning
confidence: 99%
“…Aging is the consequence of cell division and a conserved natural process among eukaryotic cells. Replicative aging is the result of asymmetric cell divisions, and is an important contributor to pathogenesis (20). During replicative aging, the fungal cell wall becomes thicker, which is associated with increased resistance to antifungals and phagocytic uptake (21, 22).…”
Section: Introductionmentioning
confidence: 99%